Congenital Hypothyroidism in the Southern Bangladesh (TAJ: Journal of Teachers Association, 2009)
Congenital hypothyroidism is the commonest preventable cause of mental retardation. It is more prevalent in endemic goiter regions like Bangladesh. But magnitude of the problem has not been studied at national level. This study was done to detect the frequency of congenital hypothyroidism in southem part of Bangladesh & to develop neonatal screening program. All the living newborns delivered between Oct 01 to June 05 Khulna Medical College Hospital were included in the study, After taking the relevant information from mother, cord blood sample were collected from the newborn within 120 hours of birth and kept in freezer. At the end of collection of each two months, the lot was sent to the laboratory of Institute of Nuclear Medicine, Dhaka for radioimmunoassay of TSH. Potential cases with TSH above 10 MIU were recalled for thyroid function test for confirmation of diagnosis. Fifteen hundred samples were collected in total during 45 months of study. One forty seven unsatisfactory samples were discarded; thereby 1353 samples were eventually assayed for TSH. Among the study population 88.2% hailed from Khulna district and the rest of the cases came from neighboring districts. Male to female baby ratio was 1.2:1. Regarding the birth weight 33.4% babies were low birth weight. TSH above 10 was found in 35 babies among whom one baby was hypothyroid and the other member of the twin was also hypothyroid although the TSH level was below 10. None of newborn had TSH level above 20. Thus frequency of congenital hypothyroidism was 1.5 per thousand living newborn. Congenital hypothyroidism in southern part of the country is quite high in relation to global incidence. Although this is not the national picture but the high figure is alarming. Therefore neonatal screening program should be implemented as soon as possible to reduce the number of mentally retarded child.   doi: 10.3329/taj.v21i1.3212 TAJ 2008; 21(1): 18-22